Bidirectional regulation of fragile X mental retardation protein phosphorylation controls rhodopsin homoeostasis. - Wang, X.; Mu, Y.; Sun, M.; Han, J. (Journal of molecular cell biology, 2017)
Homoeostatic regulation of the light sensor, rhodopsin, is critical for the maintenance of light sensitivity and survival of photoreceptors. The major fly rhodopsin, Rh1, undergoes light-induced endocytosis and degradation, but its protein and mRNA levels remain constant during light/dark cycles. It is not clear how translation of Rh1 is regulated. Here, we show that adult photoreceptors maintain a constant, abundant quantity of ninaE mRNA, which encodes Rh1. We demonstrate that the Fmr1 protein associates with ninaE mRNA and represses its translation. Further, light exposure triggers a calcium-dependent dephosphorylation of Fmr1, which relieves suppression of Rh1 translation. We demonstrate that Mts, the catalytic subunit of protein phosphatase 2A (PP2A), mediates light-induced Fmr1 dephosphorylation in a regulatory B subunit of PP2A (CKa)-dependent manner. Finally, we show that blocking light-induced Rh1 translation results in reduced light sensitivity. Our results reveal the molecular mechanism of Rh1 homoeostasis and physiological consequence of Rh1 dysregulation.